Parade participants in car displaying "Moral Majority" sign - Sahl, Ted (photographer):::Creator::::::::::::
Three participants ride in convertible car during a parade. American flags drape from the backend of the car and a "Moral Majority" sign is attached to the passenger side door. One man wears a skeleton mask and American flag suit, second man wears a shirtless devil costume, and woman wears a skirt made to look like the American flag.